Meningkatkan Motivasi Siswa Melalui Model Pembelajaran Kompetisi Kelompok dalam Pembelajaran Atletik dengan Menggunakan Permainan Sirkuit Formula 1 - Afrillan, Muhammad Bintang; Lengkana, , Anggi Setia; Supriyadi, Tedi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to increase motivation to learn PJOK in athletics in the Formula 1 game among fifth-grade students at SDIP Ummul Mukminin through the use of a modified learning model. This research uses the classroom action research (PTK) method. This research was carried out in two cycles, starting with a pre-cycle and then each cycle consisting of planning, action, observation, and reflection. The subjects of this research were class V students at SDIP Ummul Mukminin for the 2023/2024 academic year with a total of 22 students consisting of 11 boys and 11 girls. The collection technique uses an observation format sheet for assessing student learning motivation and a format for assessing student skills. The data analysis technique used in this research is a mixed method which includes quantitative and qualitative data. In conclusion, modifying the ball can increase student learning motivation and student learning outcomes in athletic learning using the Formula 1 circuit game through a group competition learning model for class V students at SDIP Ummul Mukminin. Keywords: athletics, competition, learning model motivation